Langerhans Cell Histiocytosis in the Oral Cavity - Maria Meildi; Kiki Akhmad Rizki; Monty Priosodewo Soemitro; Maman Abdurahman; Raden Yohana; Bethy S Hernowo (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Langerhans cell histiocytosis (LCH) is a rare hematological malignancy. The incidence of this disease is only 1% of soft tissue and lymph node cancer. Clinical manifestations and organ involvement vary widely. Lesions in the oral cavity are rare. LCH occurs more often in children, 10 times more often than in young adults. Case presentation: A 20-year-old male came with the main complaint of a lump on the roof of the mouth and the right inner cheek. Physical examination of the face and oral cavity found a mass attached to the palate 1x1x1 cm with the same color as the surrounding tissue, flat surface, soft consistency, could be moved, and a mass was found in the left buccal 2x2x2 cm, with the same color as the surrounding tissue, flat surface, cystic consistency, not fixed and can be moved. Hematology laboratory examination was within normal limits, so no examination was carried out for bone marrow puncture (BMP). From the results of a CT scan of the head and neck, a solid mass was found with a hypodense part in it in the right buccal area attached to m. right masseter, and in the left hard palate area, which was suggestive of Langerhans cell histiocytosis. The results of histopathological examination of the lesion which underwent an incisional biopsy showed positive S100 and CD1a, this patient was diagnosed with Langerhans cell histiocytosis LCH. Next, this patient was treated with excision of the mass in the palate and buccal area. The patient was treated in the surgical inpatient department for 2 days, and the postoperative wound was in good condition. Conclusion: Cases of Langerhans cell histiocytosis (LCH) are very rare cases that have different clinical symptoms depending on the organs involved, so it is important to understand this disease better. In this case, it was unilocal LCH without the involvement of other organs, so only local therapy was carried out in the form of surgical excision and observation was carried out after 3 months after surgery with the results of the wound improving without any new lumps appearing.